Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10278-016-9922-9
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Estimation of Volumetric Breast Density Using Artificial Neural Network-Based Calibration of Full-Field Digital Mammography: Feasibility on Japanese Women With and Without Breast Cancer

Abstract: Breast cancer is the most common invasive cancer among women and its incidence is increasing. Risk assessment is valuable and recent methods are incorporating novel biomarkers such as mammographic density. Artificial neural networks (ANN) are adaptive algorithms capable of performing pattern-to-pattern learning and are well suited for medical applications. They are potentially useful for calibrating full-field digital mammography (FFDM) for quantitative analysis. This study uses ANN modeling to estimate volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…There is a great deal of overlap between detection and classification with CNNs in mammography as many CNNs designed for detection also ultimately aim to classify lesions. Additional applications in breast imaging include accurate classification of breast density on mammograms (38) and classification of tumors (9).…”
Section: Classificationmentioning
confidence: 99%
“…There is a great deal of overlap between detection and classification with CNNs in mammography as many CNNs designed for detection also ultimately aim to classify lesions. Additional applications in breast imaging include accurate classification of breast density on mammograms (38) and classification of tumors (9).…”
Section: Classificationmentioning
confidence: 99%
“…It is reported that AI has been used in medical work such as disease diagnosis and screening (45)(46)(47)(48)(49) and is used to predict the occurrence of perioperative adverse events by establishing large databases and machine deep learning (50,51). In the prevention and control of COVID-19, AI has shown even more great advantages and value in adjunctive diagnosis, image analysis, drug development, temperature detection, robotic disinfection, pandemic modeling, and health management (52)(53)(54).…”
Section: Ai Technologymentioning
confidence: 99%
“…It gives a broader range of resolution and densities in dense breasts with minimal noise during image accession [15]. It does not require additional images or exposure of patients to unnecessary radiation and uncomfortable tests for the processing of breast images [16]. DM has given a platform to the CAD software that is used to produce data in digital formats with improved sensitivity in the dense breasts in pre-or postmenopausal females or females under the age of 50 years [17].…”
Section: Digital Mammographymentioning
confidence: 99%